Complex scientific and technical programs and information requirements - Zenona Atkočiūnienė; Romualdas Broniukaitis (Knygotyra, 1988)
The peculiarities of modern social development have determined the increase in national economy management and planning standards. Complex scientific and technical programs serve the timely and effective solution of major social and economic problems.